Changes in Editorial Board - Renuka Jindal (IEEE Journal of the Electron Devices Society, 2016)
Due to ever increasing demands on his time, Prof. Mehdi Anwar is moving on from the editorial board of J-EDS. As a member of the founding Editorial Board I want to thank Mehdi for his support in the formative years of the publication. He did an excellent job in enforcing the highest standards of quality of the finished manuscripts while at the same time lending a helping hand to the authors. This spirit has been the hallmark of J-EDS since its inception in 2013. Mehdi we wish you all the best in your future endeavors.